The Hands-on Learning Impact to Learning Engagement - Thiri, Yoon; Oo, May Thazin; Ko, Aye Nandar; Paw, Naw Ta Mu Lar; Guirguis, Joan Mel (11th International Scholars Conference, 2024)
At Asia Pacific International University in the Education Department, education major students need to manipulate different hands-on activities in their learning requirements. Hands-on learning is an activity in which students need to manipulate their psychomotor skills and they learn and gain a better understanding of this skill through experience. So, this research aims to measure how these hands-on activities learning impact the learning engagement of education major students. This study is a quantitative method and will be done by using random sampling. The 20-items self-constructed instruments was utilized in this study. The researchers used random sampling technique to select the participants for the study. There were 95 participants of which 31 are males and 64 are females. Study revealed a positive correlation between Hands-on Learning and Learning Engagement.